2017
DOI: 10.1371/journal.pone.0174434
|View full text |Cite
|
Sign up to set email alerts
|

Sports-related sudden cardiac deaths in the young population of Switzerland

Abstract: BackgroundIn Switzerland, ECG screening was first recommended for national squad athletes in 1998. Since 2001 it has become mandatory in selected high-risk professional sports. Its impact on the rates of sports-related sudden cardiac death (SCD) is unknown.ObjectiveWe aimed to study the incidence, causes and time trends of sports-related SCD in comparison to SCD unrelated to exercise in Switzerland.MethodsWe reviewed all forensic reports of SCDs of the German-speaking region of Switzerland in the age group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…A recent European study reported an autopsy rate in young sudden death of less than 50%. 45 Where autopsy is not used, cause of death may be misclassified, although the impact of this misclassification on overall incidence is uncertain. In some cases, cause of death may remain uncertain even after autopsy.…”
Section: Open Accessmentioning
confidence: 99%
“…A recent European study reported an autopsy rate in young sudden death of less than 50%. 45 Where autopsy is not used, cause of death may be misclassified, although the impact of this misclassification on overall incidence is uncertain. In some cases, cause of death may remain uncertain even after autopsy.…”
Section: Open Accessmentioning
confidence: 99%
“…SCD in young people has an estimated incidence of 0.46-3.7 events per 100000 person-years and it is more frequent in men than women as summarized in Table 1 [ 8 , 9 ]. In young people it relates to channelopathies and cardiomyopathies [ 10 14 ], myocarditis and substance abuse [ 15 – 20 ]. The risk of SCD increases with age due to the higher prevalence of coronary artery disease (CAD), valvular heart diseases and heart failure (HF) in older age [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…SCD might be the first finding in these completely asymptomatic, previously healthy children. 21,22 This condition also leads an ongoing debate in medical screening of sports preparticipation and lack of a standard method. In addition, there is no study for the efficacy or cost-effectiveness of different procedures applied in our country.…”
Section: Discussionmentioning
confidence: 99%